2011
DOI: 10.1172/jci45680
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of insulin secretion and the clinical implications for obesity and diabetes

Abstract: Insulin secretion is a highly dynamic process regulated by various factors including nutrients, hormones, and neuronal inputs. The dynamics of insulin secretion can be studied at different levels: the single β cell, pancreatic islet, whole pancreas, and the intact organism. Studies have begun to analyze cellular and molecular mechanisms underlying dynamics of insulin secretion. This review focuses on our current understanding of the dynamics of insulin secretion in vitro and in vivo and discusses their clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
319
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(341 citation statements)
references
References 120 publications
18
319
0
4
Order By: Relevance
“…To directly test this idea, we incubated β cells for 1 hour with 20 mM glucose and 10 nM glucagon-like peptide-1 (GLP-1), an incretin peptide that increases insulin secretion through cAMPand VAMP8-dependent mechanisms (68). Indeed, the treatment revealed a significant decrease of insulin granule density under TIRFM in KO β cells (Figure 8, F and G), suggesting a defect of insulin granule recruitment during GSIS, which is consistent with the proposed actin function in granule replenishment (11,61).…”
Section: And E)supporting
confidence: 72%
See 3 more Smart Citations
“…To directly test this idea, we incubated β cells for 1 hour with 20 mM glucose and 10 nM glucagon-like peptide-1 (GLP-1), an incretin peptide that increases insulin secretion through cAMPand VAMP8-dependent mechanisms (68). Indeed, the treatment revealed a significant decrease of insulin granule density under TIRFM in KO β cells (Figure 8, F and G), suggesting a defect of insulin granule recruitment during GSIS, which is consistent with the proposed actin function in granule replenishment (11,61).…”
Section: And E)supporting
confidence: 72%
“…The second possibility is that dynamin-induced actin reorganization retards granule recruitment at a later stage of secretion. This is supported by the positive role of actin in vesicle transport (64)(65)(66)(67) and the pronounced defect in the second-phase secretion (Figure 3), which largely relies on new granule recruitment to the PM (8,11). To directly test this idea, we incubated β cells for 1 hour with 20 mM glucose and 10 nM glucagon-like peptide-1 (GLP-1), an incretin peptide that increases insulin secretion through cAMPand VAMP8-dependent mechanisms (68).…”
Section: And E)mentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, it is reasonable to speculate that the profile of miRNAs present in the β-cell may have diversified to specifically suppress these genes due to their unique functional mandate: to systematically regulate insulin release. It is widely reported that the β-cell releases only a small percentage of its stored granule pool in response to glucose further supporting the notion that exocytosis from the β-cell is a highly regulated process [29] [28]. Therefore the presence of miRNAs may simply serve to manage and synchronize the efficient output of insulin.…”
Section: Identification Of Microrna Targets In the β-Cellmentioning
confidence: 77%